Aaron Marking a House with a Tau Cross: Typological Significance of the Scene in Rheno-Mosan Art of 12th Century - Sycheva, Iuliia A. (Actual Problems of Theory and History of Art, 2023)
One of the characteristic features of the Rheno-Mosan iconography in the 12th century is an appeal to typological logic in the selection and systematization of the episodes that form a pictorial cycle. Among the themes that are repeatedly encountered in the surviving cycles and in a number of scattered fragments, there is the scene of marking the door with the letter Tau (Ex 12:22). Based on the analysis of the iconographic cycles of the surviving or reconstructed works of Rheno-Mosan art, the article attempts to characterize the compositional and semantic role in the pictorial cycle of the subject under consideration. This episode is one of the most frequent prototypes, however, it is presented in different ways in different groups of objects (it is often used in the iconography of crosses and is not found in currently known portable altars). The connection with the theme of the Cross as a saving sign brings this episode closer to another Old Testament type, the scene from the prophecy of Ezechiel about marking the sign on the foreheads, which is reflected in the iconography of these two scenes (at the level of attributes and inscriptions) and is comprehended in the general solution of the iconographic program. In addition to works of art, the article mentions textual sources of the 12th century, in which the subject under consideration is interpreted in a number of other typological scenes.